PENGARUH KEPEMIMPINAN KEPALA SEKOLAH ABAD 21, BUDAYA MUTU DAN KEPUASAN KERJA TERHADAP KINERJA GURU DI SD NEGERI KECAMATAN BAKUMPAI KABUPATEN BARITO KUALA - Shalahuddin Al-Ayubi; Muhammad Yuliansyah; Hengki Hengki (Bajang Institute, 2023)
The background of this research is that there are still public elementary school teachers in Bakumpai District who have less than ideal performance, from the aspects of lesson planning, implementation of learning to learning evaluation. This study aims to analyze: 1) 21st century principal leadership, quality culture, job satisfaction and performance of public elementary school teachers in Bakumpai District, 2) Direct influence of 21st century principal leadership on job satisfaction, 3) Direct influence of quality culture on satisfaction work, 4) The influence of the leadership of 21st century school principals on teacher performance, 5) The influence of quality culture on teacher performance, 6) The direct effect of job satisfaction on teacher performance, 7) The influence of the leadership of 21st century principals indirectly on teacher performance through satisfaction work, 8) Indirect influence of quality culture on teacher performance through job satisfaction.This research is a descriptive correlational study with path analysis. The study population was all 97 public elementary school teachers in Bakumpai District with a population sample of 97 because the population was less than 100. Data were collected through questionnaires and documentation and then analyzed descriptive and inferential statistics through SPSS 25.The results of the study show: 1) There is a direct influence of the 21st century principal's leadership on teacher job satisfaction. 2) There is a direct influence of quality culture on teacher job satisfaction. 3) There is a direct influence of the 21st century principal's leadership on teacher performance. 4) There is a direct influence of quality culture on teacher performance. 5) There is a direct effect of job satisfaction on teacher performance. 6) Indirectly, the leadership of the 21st century principal affects performance through job satisfaction. 7) Indirectly quality culture influences performance through job satisfaction. 8) 21st century principal leadership, quality culture, job satisfaction and performance of public elementary school teachers in Bakumpai District, Barito Kuala Regency, are in the moderate category.Conclusion: Principal leadership and quality culture directly or indirectly have a positive and significant effect on job satisfaction and teacher performance.